The Commitment of a Headmaster Leadership of Learning to Improve the Quality of Education: The Commitment of a Headmaster Leadership of Learning to Improve the Quality of Education - Jumaria Sirait (Jurnal Mantik, 2020)
This research aims to find out (1) Commitment towards the school’s vision in executing the task and function; (2) Establishing the school’s vision as a guidelines in managing and leading the school; and (3) constantly focusing the activities towards learning and improving teacher’s quality in class. Leadership in teaching is one of the skill necessary as a headmaster. Leadership in teaching is very important to be applied because: (1) it could improve the student’s performance significantly; (2) it could encourage and instruct the school body to improve their student’s performance; (3) it could help the school body to focus their activities to achieve the school’s vision, mission and; (4) it could help the establishment of the school’s learning community and shape the school into an educative school. Leadership in teaching consist of the aptitude of the headmaster to formulate and to communicate the purpose of the school, supervising, guiding, and giving feedback in learning. The basic principle of headmaster leadership is in fact the same with any leadership within organisations around, which is the will to give influence to others (staff) in order for them to participate in achieving goals that been set. In order for this goals to be achieved, there are four basic that must be applied by the headmaster in executing its leadership task, which are planning, organizing, leading and monitoring. Next, three main point that must not be missed by the headmaster in attempt to improve the quality of education: (1) reinforcing curriculum; (2) improving the capacity of school management; and the teacher’s competence.